How Enterprise Education Can Promote Deep Learning to Improve Student Employability. (December 2013) - Moon, Rob; Curtis, Vic; Dupernex, Simon
This paper focuses on identifying the approaches students take to their learning, with particular regard to issues of enterprise, entrepreneurship and innovation when comparing the traditional lecture format to a more applied, practice-based case study format. The notions of deep and surface learning are used to explain student learning. More active methods of teaching (such as discussion and case studies) promote a deep approach; and work elsewhere has suggested that these methods are more effective than lectures for the promotion of thought. For this study, questionnaire surveys were used to determine whether there was a difference in approach to learning between most and least beneficial course modules, and between the lecture-based and more applied, practice-based case study formats. The findings indicated that deeper learning results from a more active approach, with students who adopted deeper learning being better able to apply their learning in different entrepreneurial contexts.